2006
DOI: 10.1068/p5319a
|View full text |Cite
|
Sign up to set email alerts
|

Dancing Shapes: A Comparison of Luminance-Induced Distortions

Abstract: We present an illusory display in which a grid of outlined squares is positioned in front of a moving luminance gradient. Observers perceive a strong, illusory, 'wavelike' motion of the superimposed squares. We compared luminance effects on dynamic and static aspects of this illusion. The dynamic aspect was investigated by means of a temporal gradient, which induced an illusory pulsing of the outlined squares. The static aspect was investigated in two different ways. In one experiment, the outlined squares wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Study of early processes in perceptual grouping has mainly focused on the role of contrast polarity, with a wide variety of tasks and stimuli: contour formation in Glass patterns ( Glass and Switkes, 1976 ; Burr and Ross, 2006 ), illusory contour formation ( Prazdny, 1983 ; Dresp and Grossberg, 1997 ; Spehar, 2000 ), line contrast detection ( Wehrhahn and Dresp, 1998 ), orientation discrimination with co-linear lines ( Brincat and Westheimer, 2000 ), perceptual closure ( Spehar, 2002 ), contour detection ( Field et al, 2000 ), illusory misalignment and tilt of contours ( Kitaoka et al, 2004 ; van Lier and Csathó, 2006 ; Guidi et al, 2011 ), and contours reassembling in perceptual transparency ( Kitaoka et al, 2001 ; Singh and Huang, 2003 ). The results of these studies reveal considerable differences in sensitivity for contrast polarity in the figural contexts examined, so that we are far from having a proper view on the extent to which this factor contributes.…”
Section: Introductionmentioning
confidence: 99%
“…Study of early processes in perceptual grouping has mainly focused on the role of contrast polarity, with a wide variety of tasks and stimuli: contour formation in Glass patterns ( Glass and Switkes, 1976 ; Burr and Ross, 2006 ), illusory contour formation ( Prazdny, 1983 ; Dresp and Grossberg, 1997 ; Spehar, 2000 ), line contrast detection ( Wehrhahn and Dresp, 1998 ), orientation discrimination with co-linear lines ( Brincat and Westheimer, 2000 ), perceptual closure ( Spehar, 2002 ), contour detection ( Field et al, 2000 ), illusory misalignment and tilt of contours ( Kitaoka et al, 2004 ; van Lier and Csathó, 2006 ; Guidi et al, 2011 ), and contours reassembling in perceptual transparency ( Kitaoka et al, 2001 ; Singh and Huang, 2003 ). The results of these studies reveal considerable differences in sensitivity for contrast polarity in the figural contexts examined, so that we are far from having a proper view on the extent to which this factor contributes.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned previously, Kitaoka (2006) has discussed the configurational coincidences between the motion, stereo and positional reversed effects described by Anstis and Rogers (1975) and the phenomenal phenomena described by Gregory and Heard (1983). Van Lier and Csath o (2006) have also noted the configurational coincidence between these effects and Cafe-Wall-like tilt illusions. The key feature common to all these effects is the presence of thin light or dark strips that are flanked on either side by regions that are either increasing or decreasing in luminance (Figure 3).…”
Section: Kitaoka's Colour-dependent Fraser-wilcox Patternsmentioning
confidence: 78%
“…Gabor units sharing the same CP are easier to perceptually group when distributed among other Gabor units (McIlhagga and Mullen, 1996 ; Field et al, 2000 ); real or illusory contours are easier to detect when of the same CP (Cavanagh and Leclerc, 1989 ; Spehar, 2000 ). Research on orientation misperception (Roncato and Casco, 2003 , 2006 ; Van Lier and Csathó, 2006 ) demonstrated that this tendency manifests locally as illusory tilts at the edge extremities when they have the same contrast polarity and extend within a spatial range of 7–15°.…”
Section: Introductionmentioning
confidence: 99%